Dissonance in the Danish Atlantic: speech, violence and mutiny, 1672–1683. Issue 2 (2nd April 2016) - Heinsen, Johan
ABSTRACT: In 1683 the fragile Danish Atlantic was shaken by a mutiny orchestrated by a coalition of common sailors and convicts. On the way to St. Thomas in the Caribbean, they seized the ship, Havmanden, and killed their superiors. Among the dead was the newly appointed governor of St. Thomas, Jørgen Iversen. He was a veteran of Atlantic colonization and had been the governor of the Caribbean colony from its foundation in 1672 to 1680. In his absence the colony had devolved into a pirate's nest, and the Danish West India and Guinea Company hoped that his experience and authority could once again bring their small empire back on track. Instead, the mutiny further weakened their grasp on their Caribbean colony. In the night before the mutiny, the governor had attempted to quell the simmering disgruntlements on the ship by promising the convicts that he would treat them well when they reached the colony. However, they heard his promise as a threat. This article explores this discrepancy and places it in the context of circulating stories and rumours of violence, exploitation and death in the Caribbean. In exploring the contours of such storytelling felt only indirectly in the fragmented archival trail, this genealogy of a single speech act, in turn, raises questions about the role of speech in the making and unmaking of seventeenth-century Atlantic empires.